Flax/ramie hybrid fibers enhanced with SiC nanoparticles - T. Sathish; Jayant Giri; R. Saravanan; Emad Makki (AIP Advances, 2024)
To create a hybrid material of ramie and flax fibers with silicon carbide (SiC) nanoparticles, it should have better thermal and mechanical properties. Across industries, sustainable materials are growing in demand for high performance, which is the impetus behind this study. A sustainable future is more about contributing to sustainable alternatives like ramie and flax fibers made from traditional synthetic materials. A key area focused on increasing strength, temperature resistance, and stiffness will be the addition of SiC nanoparticles to hybrid fibers. The research process carefully mixes the ramie and flax fibers with SiC nanoparticles to achieve optimal flexibility, thermal stability, and balance of strength. Hybrid material is examined using characterization techniques such as mechanical testing and scanning electron microscopy to determine the functioning of the microstructure. The possibility of composite material recycling, the impact of hybrid fibers, and accounting for natural fibers for sustainability are considered possible in this research. It should be innovative material development that has significant implications from the findings that meet environmental sustainability goals and satisfy performance requirements.